ANALYSIS OF THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, AND RETURN ON EQUITY ON FIRM VALUE IN TRANSPORTATION SECTOR COMPANIES - Wilhelmina Muni; Moni Yuniati Siahaan; Irena Juniarti Veranda Rea (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the influence of the Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Equity (ROE) on firm value, which is proxied by Price to Book Value (PBV), in transportation sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period.Methods: A quantitative, associative design was employed, using secondary data from annual financial reports. The analysis was conducted using multiple linear regression after fulfilling classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests.Results: Based on the results of data analysis and discussion regarding the influence of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Equity (ROE) on Firm Value (PBV) in transportation sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024, it can be concluded that the financial condition of transportation sector companies shows quite high variation. The average Current Ratio (CR) of 1.25 indicates a relatively good short-term liquidity capability, although there is substantial variation between companies. The average Debt to Equity Ratio (DER) of 1.06 indicates a balanced capital structure between equity and debt, yet with a large variation among the companies. The average Return on Equity (ROE) of –0.039 shows that, in general, transportation companies still have low profitability performance, even tending to be negative in several companies. Meanwhile, the average firm value (PBV) of 1.62 indicates that the market still provides a positive valuation of companies’ prospects in this sector, although the internal financial condition has not yet been fully stable.Overall, it can be concluded that the Debt to Equity Ratio (DER) is the most influential variable affecting the firm value of transportation sector companies. This demonstrates that capital structure plays an important role in investors’ perception of firm value, while liquidity (CR) and profitability (ROE) have not yet become the main indicators in determining the market value of transportation companies in Indonesia. Keywords: Current Ratio, Debt-to-Equity Ratio, Firm Value, Return on Equity, and Transportation.